Application value of Early-Follicular Phase Long-Acting Gonadotropin-Releasing Hormone Agonist Long Protocol in patients with resistant ovary syndrome - Fan Zhang; Huixia Zhang; Hui Du; Xin Li; Haixia Jin; Gang Li (BMC, 2023)
Abstract Background Resistant ovarian syndrome(ROS) is a rare disease. It is difficult to diagnose and treat. Most of the literature reports on assisted pregnancy treatment for ROS patients are individual case reports. In this paper, the ovulation stimulation protocol and assisted pregnancy process of ROS infertile patients in our reproductive center were summarized and analyzed to provide information and support for the clinical treatment of ROS patients. Methods From January 2017 to March 2022, assisted reproductive technology treatments and clinical characteristics parameters of six patients with ROS were retrospectively reviewed. Based on controlled ovarian stimulation protocols, these stimulation cycles were separated into four groups: Early-Follicular Phase Long-Acting Gonadotropin-Releasing Hormone Agonist Long Protocol (EFLL) group (n = 6), Progestin Primed Ovarian Stimulation(PPOS) protocol group (n = 5), mild-stimulation protocol group (n = 2), and Natural cycle protocol group (n = 3). Results A total of 16 cycles of ovulation stimulation were carried out in 6 patients with ROS. A total of 19 oocytes were retrieved, as well as 13 MII oocytes, 11 two pronuclear(2PN) fertilized embryos, and 8 excellent embryos. The oocytes acquisition rate was 50% and the fertilization rate of 2PN was 57.9%, and the excellent embryo rate was 72.7%. The EFLL protocol obtained 17 oocytes, 12 MII oocytes, 11 2PN fertilized embryos, and 8 excellent embryos; the mild-stimulation protocol obtained 1 oocyte; the Natural cycle protocol obtained 1 oocyte, and oocytes were not matured after in vitro maturation (IVM); the PPOS protocol obtained no oocytes. Compared with three other protocols, The fertilization rate of 2PN (64.7%) and excellent embryo rate (72.7%) in the EFLL protocol were higher than those of other protocols(0%). Two fresh cycle embryo transfers resulted in live births, while two frozen-thawed embryo transfer cycles resulted in one live birth and one clinical pregnancy using the EFLL protocol. Conclusion Although the current study is based on a small sample of participants, the findings suggest that the EFLL protocol can be employed for ovarian stimulation and may result in a live birth in ROS patients.